2021
DOI: 10.18639/merj.2021.1431686
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Networking Strategic Renewal and Performance of Youth-Owned Agro-Processing Small and Medium Enterprises in Selected Counties in Kenya

Abstract: The current business environment has become very dynamic and this comes with threats and opportunities. Some of the factors that pose challenge in this environment are new entrants, loss of competitive advantage or rapid change of technology. In Kenya, SME suffer the same fate despite the critical role they play in the country. Most of the youth business startups fail at their third year and very few enterprises have grown into large formal organizations. To survive under this dynamic environment, entrepreneur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This study uses a qualitative approach; the study's results explain that companies need ways and methods to achieve the strategic renewal process better for better firm performance. Kariuki et al (2021) discuss strategic renewal on firm performance. Strategic renewal is used in this study, namely entrepreneurial networking from members of social networks, professional networks, business networks, and social networks.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This study uses a qualitative approach; the study's results explain that companies need ways and methods to achieve the strategic renewal process better for better firm performance. Kariuki et al (2021) discuss strategic renewal on firm performance. Strategic renewal is used in this study, namely entrepreneurial networking from members of social networks, professional networks, business networks, and social networks.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agarwal & Helfat (2009) first analyzed early studies on strategic renewal and noted that the term is frequently discussed but infrequently defined. Study on company performance and strategic renewal has begun in numerous nations (Kaipainen & Aarikka-Stenroos, 2022;Kariuki et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In point of fact, these data demonstrated that a significant number of small and medium-sized enterprises (SMEs) join and depart these marketplaces on an annual basis, with a turnover rate of around 32 percent. Therefore, Kariuki (2023) argued that entrepreneurial marketing technique is essential for agro-based youth small and medium-sized enterprises (SMEs) in Kenya to maintain a sustained competitive advantage. Further, in order to address the performance of youth small and medium-sized enterprises (SMEs), the World Bank (2022) emphasized that entrepreneurial practices are an important survival tool for agro-based youth SMEs that are operating in a dynamic environment.…”
Section: Statement Of the Problemmentioning
confidence: 99%
“…Van Erkelens, Thompson, and Chalmers (2023) define entrepreneurial practices as established and systematic methods or a domain of activities that include the application of knowledge and the process of change in the area of entrepreneurship. Kariuki (2023), claim that the SME sector has shown low adoption of entrepreneurial methods. Furthermore, the small number of youth SMEs in the agricultural sector who embrace entrepreneurial techniques tend to use informal, unorganized, and non-planned approaches.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the formal sector has not met the challenges of employment creation (Kerubo, 2023). To help address youth unemployment in Kenya, the National and County Governments with donors support crafted youth agro entrepreneurship development (Kariuki, 2023), through small and medium agro based youth enterprises startups for instance, traders, producers, aggregators, and transporters sitting at transitional points in the agriculture value chain (Odhiambo et al, 2020), but unfortunately while some SMEs grow, more than 50% fails to take off, collapsed and some failed to reach maturity. That is, Kenya Economic Outlook (2022) survey reports indicate that more than 50% of SMEs in Kenya are known for their low startup, low working capital and low growth rate.…”
Section: Statement Of the Problemmentioning
confidence: 99%